New professional competencies in the era of WEB 2.0 and 3.0 and the dissemination of ICT - Rudewicz, Jacek; Sala, Krzysztof (Przedsiębiorczość - Edukacja, 2021)
The purpose of this article is to identify and describe the new, yet relatively poorly known, competencies related to WEB 2.0 and 3.0 and the dynamically changing organisational environment influenced by the development of ICT. The article’s content can be used (application purpose) to draw attention to the necessity of active searching for new competency areas by trainers and teachers. To achieve this aim, two research tasks were undertaken. The first was a literature review and explanation of the concepts related to the research subject. This theoretical foundation then served as a starting point for an attempt to create a list of professions and related competencies corresponding to the needs of WEB 2.0 and 3.0. The results of this are presented in a tabular form.